2010
DOI: 10.1017/s0008423910000648
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Links between Party and Appointment: Canadian Federal Judicial Appointments from 1989 to 2003

Abstract: Abstract. Studies of federal judicial appointments made before 1988 discovered significant partisan ties between judicial appointees and the governments appointing them. In 1988, in response to criticism of these “patronage appointments,” the Mulroney government introduced screening committees to the process. This article explores the impact of these committees. Using information gained from surveys of legal elites, we trace the minor and major political connections of federal judicial appointees from 1989 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 5 publications
0
24
1
Order By: Relevance
“…with the governing party. The trends were relatively consistent between Conservative and Liberal governments~see Hausegger et al, 2010, for a detailed description of all these data!.…”
Section: Judicial Process and Selectionmentioning
confidence: 67%
See 1 more Smart Citation
“…with the governing party. The trends were relatively consistent between Conservative and Liberal governments~see Hausegger et al, 2010, for a detailed description of all these data!.…”
Section: Judicial Process and Selectionmentioning
confidence: 67%
“…The majority of candidates are promoted from a lower court and do not go through the committee process at this stage. However, the minister typically undertakes consultations with the legal community before promoting someone~for a more detailed description of the appointment process, see Hausegger et al, 2010!. Our earlier research on federal judicial appointments following the introduction of the screening committees shows that for the 1989 to 2003 time period 27 per cent of provincial appeal court appointees had "major" participation with the governing party that appointed them~such as campaign organizing or close social ties to a cabinet minister!, and 15 per cent had more "minor" activities and associations~political donations, minor constituency work! with the governing party.…”
Section: Judicial Process and Selectionmentioning
confidence: 99%
“…Looking at appointments by province helps to further unpack how party connection may adversely affect the likelihood that women will be appointed to the bench. Previous research has found that the number of judges with political connections varies dramatically by province (Hausegger et al, 2010; Russell and Ziegel, 1991). For example, whereas about 14 per cent of British Columbia's appointees had connections to the party in power between 1989 and 2003, this number was an astounding 90 per cent for Prince Edward Island (Hausegger et al, 2010: 643–646).…”
Section: Resultsmentioning
confidence: 99%
“…Relying exclusively on financial contributions means that other types of more substantive political involvement, such as being a party member, fundraising or running for political office, are excluded. Indeed, Hausegger and colleagues found that between 1989 and 2003 approximately 22 per cent of federal judicial appointees had major connections and/or major activities with the party in power (Hausegger et al, 2010: 647). Further, this article does not try to disentangle the different reasons why party connections may play an important role for judicial appointments, such as signaling a complementary political ideology, personal or professional connections, or as repayment for past political service.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation